Mass screening for hepatitis B and C in Southern Upper Egypt - Gamal Soliman; Mahmoud S. Elzalabany; Tarek Hassanein; F. DeWolfe Miller (BMC, 2019)
Abstract Background It is well documented that Egypt has the highest prevalence of hepatitis C virus (HCV) infection in the world. The recent development of highly effective direct acting antiviral drugs (DAAs), has opened the possibility of treating and curing HCV infection in the Egyptian population on a large scale. Methods A screening demonstration project was implemented in southern Egypt in and around the city of Luxor. Free screening and if indicated, treatment, was offered to those 16 years or older for anti-HCV antibodies (anti-HCV) and hepatitis B surface antigen (HBsAg) using third generation enzyme immunoassays (Enzygnost® Anti-HCV and HbsAg). Statistical methods included estimation of odds ratios (OR) and 95% confidence intervals (95% CI). Results There was a large turnout of 67,042 persons who were screened in a 12-month period starting in June 2016. Thirty-one thousand nine hundred sixty-four males (47.7%) and 35,074 females (52.3%) were screened with a mean age of 43.6 ± 14.3 years. Nine thousand seven hundred one patients (14.5%) were positive for anti-HCV and 2950 (4.4%) for HBsAg. Prevalence of anti-HCV was significantly higher in males than females (19.67% vs.9.73% OR = 2.27; CI 2.2 to 2.4; p < 0.001) and the same for HBsAg (6.2% vs. 2.8% OR = 2.3; CI 2.2 to 2.5; p < 0.001). The prevalence of anti-HCV was significantly associated with age (p < 0.001), ranging from between 1 and 4% in individuals below the age of 40 years, then increased steadily to 42% at age 60 followed by a precipitous decline in age specific prevalence. Conclusions The results showed unanticipated patterns in the Luxor area of anti-HCV and HBsAg by age and gender in contrast to previous reports on this unique HCV epidemic in Egypt. Moreover, the level and rate of turnout, cost, and other logistical issues, provided essential information for effective planning, design, and evaluation methods for larger national mass screening and treatment programs.